Prevalence of endo-perio lesions according to the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Disease in a university hospital - Rütters, Maurice; Gehrig, Holger; Kronsteiner, Dorothea; Schüßler, Dorothée L.; Kim, Ti-Sun (Quintessence international, 2022)
Objectives: Teeth with combined endodontic-periodontal lesions (EPLs) have favorable to hopeless prognoses. The new classification system was developed by the World Workshop on the Classification of Periodontal and Peri-Implant Disease in 2017 and suitable epidemiologic data related to this new system are currently lacking. This study aims to contribute data about the prevalence of EPLs according to the new system. Method and materials: A total of 1,008 panoramic views taken in 2019 were analyzed, recording the presence of an EPL and other periodontic parameters. Radiographs of bad quality and of the same person were excluded. Additionally, the EPLs' radiographic patterns were rated by two raters according to their shape (j-shaped vs cone-shaped). Descriptive statistical methods as well as t tests for continuous and chi-squared tests for categorical variables were used. Results: Overall, 866 patients (with 18,963 teeth) were included. Prevalence of EPLs was 4.9% (n = 43) (patient-related)/0.4% (n = 71) (tooth-related). Mean age (62.3 years vs 51.5 years), mean maximal percentage of bone loss (60% vs 30%), and mean age-adjusted bone-loss index (1.0 vs 0.6) were considerably higher compared to patients without EPL. A total of 67 EPLs were found in patients with stage III/IV periodontitis and 4 in patients with stage II periodontitis. Conclusions:This is the first study showing prevalence of EPLs (4.9%/0.4%) according to the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Disease. Patients with EPLs have a substantially higher maximal percentage of bone loss and a higher age-adjusted bone-loss index at residual teeth, excluding teeth with EPLs. All patients have at least stage II periodontitis.
Gesehen am 27.07.2022